Efektivitas Model Pembelajaran Project Based Learning (PjBL) terhadap Minat dan Hasil Belajar Siswa - Isrohani Hamidah; Sinta Yulia Citra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on student interest and learning outcomes at SMA Negeri 4 Seluma. The method used is a quasi-experimental (Quasi Experiment) with a randomized control group pretest-posttest design. The results showed that students' interest and learning outcomes in the experimental class (XI IPA 1) were higher than the control class (XI IPA 2) with a Sig. (2-tailed) of 0.000. In conclusion, the Project Based Learning (PjBL) model is effectively used as a learning model for students' interest and learning outcomes in biology at school. Keywords: Learning Outcomes, Interest in Learning, Project Based Learning